Habitat selection and foraging strategy of American Black Ducks Anas rubripes wintering in Tennessee, USA - Osborn, Joshua M.; Hagy, Heath M.; McClanahan, Matthew D.; Davis, J. Brian; Grey, Matthew J. (Wildfowl, 2021)
American Black Duck Anas rubripes populations in North America have declined over the last 20 years, especially in the Mississippi Flyway. The Tennessee River Valley of west-central Tennessee historically has been an important winter terminus for Black Ducks in the Mississippi Flyway, but there is limited information on habitat resource selection during winter to guide management for this species. Available habitat resources and Black Duck behaviour were studied at the Tennessee and Cross Creeks National Wildlife Refuges during December–February in winters 2011/12–2012/13, and the Black Ducks’ activities were compared to a broader community of dabbling ducks Anatini sp. wintering in the same area. Black Ducks used wooded wetlands and flooded agriculture at a greater relative frequency than other available wetland types throughout winter, but foraged more in moist-soil and mudflats than in other wetland types. They selected foraging patches independent of measured food densities, but the density of food at selected foraging sites did not decline throughout winter in line with resources available in the larger landscape, indicating that the ducks may have selected foraging patches at densities above critical food densities rather than distributing optimally according to total food densities. Factors other than absolute food abundance likely influence resource selection by Black Ducks and, despite some use of flooded agricultural fields, their behaviour and use of resources indicate that they are not likely food-limited during winter at these refuges. Management for Black Ducks in western Tennessee should include a complex of natural wetland types, including forested and moist-soil wetlands, within sanctuaries where disturbance is limited.